2016
DOI: 10.1039/c5mb00577a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential COPD genes based on multi-omics data at the functional level

Abstract: Chronic obstructive pulmonary disease (COPD) is a complex disease, which involves dysfunctions in multi-omics. The changes in biological processes, such as adhesion junction, signaling transduction, transcriptional regulation, and cell proliferation, will lead to the occurrence of COPD. A novel systematic approach MMMG (Methylation-MicroRNA-MRNA-GO) was proposed to identify potential COPD genes by integrating function information with a methylation profile, a microRNA expression profile and an mRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 119 publications
0
7
0
Order By: Relevance
“…However, because dysregulation at different molecular levels and anatomical locations can dominate in different disease subgroups, multi-omics integration may be necessary to facilitate the diagnosis and understanding of disease mechanisms involved in the underlying COPD disease subgroups [4][5][6][7][8]. Several recent studies integrating two or three omics data blocks have indicated that integrating data from multiple molecular levels improves the identification of biomarkers [9,10], sub-phenotype prediction [11,12] and mechanistic understanding [13] of COPD. While these specific examples provide convincing evidence of the advantages of omics integration, no quantitative evaluation of the gain in statistical power beyond dual and triple omics integration has yet been published.…”
Section: Introductionmentioning
confidence: 99%
“…However, because dysregulation at different molecular levels and anatomical locations can dominate in different disease subgroups, multi-omics integration may be necessary to facilitate the diagnosis and understanding of disease mechanisms involved in the underlying COPD disease subgroups [4][5][6][7][8]. Several recent studies integrating two or three omics data blocks have indicated that integrating data from multiple molecular levels improves the identification of biomarkers [9,10], sub-phenotype prediction [11,12] and mechanistic understanding [13] of COPD. While these specific examples provide convincing evidence of the advantages of omics integration, no quantitative evaluation of the gain in statistical power beyond dual and triple omics integration has yet been published.…”
Section: Introductionmentioning
confidence: 99%
“…Our work reveals that key transcription factors involved in stem cell maintenance are deregulated in COPD, with in particular their expression repressed when in presence of TGF-β, bringing a molecular perspective to the cellular data. All the transcription factors that we identified are involved in lung epithelium stem/progenitor cells or in COPD, and SOX2 and ELF5 are particularly relevant as they have been shown to be required for maintenance and differentiation of lung epithelium stem/progenitor cells [1418]. Slug knockdown shows that in COPD these transcription factors are repressed downstream of Slug.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, genes, proteins, and metabolite networks are particularly important, as the explanatory value of any single molecule is small compared with multiple biomarkers [8]. These biomarkers, either in multiple biomarker panels or integrated with other omics, may lead to novel diagnostic and prognostic tests for COPD phenotypes [9]. A system-biology platform that stems from advancements in medical diagnosis, omics, and bioinformatics could offer great potential to better understand the complexity of COPD [4].…”
Section: Discussionmentioning
confidence: 99%
“…Given the current progress in next-generation sequencing and mass spectrometry, considerable attention has been paid to both omics approaches and biomarker discovery for clarifying these heterogeneous diseases [2,3,9]. However, despite accumulating evidence from genomics and transcriptomics, the application of proteomics has been limited [10][11][12].…”
Section: Introductionmentioning
confidence: 99%